The Role of Islamic Banking in Economic Growth: Financial Deepening and Bank Efficiency - Nurul Inayah; Azhari Akmal Tarigan; Isnaini Harahap (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The success of economic development is reflected in the level of welfare experienced by the society. According to data from the Financial Services Authority (OJK), the Islamic economy has become one of the largest contributors to the national economy, accounting for 46 percent of the total GDP. This study aims to analyze the role of Islamic banking in supporting economic growth in Indonesia. Method: A quantitative approach is employed using secondary monthly time series data covering the period from January 2018 to December 2023. The research applies the Vector Autoregressive (VAR) method in its restricted form, known as the Vector Error Correction Model (VECM), using EViews 12 software. The variables used include total financing (TP) as a proxy for financial deepening, BOPO as a proxy for banking efficiency, FDR as a proxy for risk management, the number of bank offices (JK) as a proxy for financial inclusion, and Gross Domestic Product (GDP) as a proxy for economic growth. Results: The results reveal that the role of the Islamic banking sector in Indonesia’s economic growth is stronger and more significant in the long run than in the short run. In the short term, total financing (TP) has not shown a significant effect on GDP, while banking efficiency (BOPO) exerts a direct and significant influence. In the long term, however, total financing and banking efficiency exhibit a more stable and significant relationship with economic growth, with Islamic banking efficiency (BOPO) contributing the most to GDP, at around 20–21%. Conclusion: These findings indicate that Islamic banking plays a pivotal role in sustaining Indonesia’s long-term economic growth, aligning with the objectives of maqāṣid al-sharī‘ah in realizing economic welfare (ḥifẓ al-māl and ḥifẓ al-nafs) and contributing to the achievement of the Sustainable Development Goals (SDGs), particularly in promoting inclusive and sustainable economic growth.